Hope and life satisfaction among Chinese shadow education tutors: The mediating roles of positive coping and perceived social support - Ji, Jie; Zhou, Linzhi; Wu, Yunpeng; Zhang, Mohan (Frontiers in Psychology, 2022)
Previous studies of the relationship between hope and life satisfaction left the underlying mechanism of how hope predicts life satisfaction unexplored to scholars. This study thus investigates the two potential mediators in the relationship between hope and life satisfaction among a sample of Chinese shadow education institution (SEI) tutors who may be under immense professional development pressure from a cross-sectional approach. The main body of the study consists of an online survey in which 221 SEI tutors reported their hope, positive coping, perceived social support, and life satisfaction. The survey results were analyzed using mediation and moderation analysis via SPSS 23.0. The results indicated that positive coping improved the relationship between hope and life satisfaction, supporting the hypothesis regarding the serial mediating effect of positive coping and perceived social support. In other words, tutors with a high level of hope tend to adopt positive coping strategies, thus will receive more social support and improve life satisfaction. Our findings revealed the independent and accumulative mediating effects of positive coping and perceived social support on the relationship between hope and life satisfaction, and had implications for the psychological intervention of SEI tutors who are currently facing enormous industry pressure.